Synthesis of a tunable ring filter: Proof‐of‐concept with fixed implementations at D‐band. Issue 9 (10th June 2021) - Rynkiewicz, Pedro; Franc, Anne‐Laure; Coccetti, Fabio; Wietstruck, Matthias; Kaynak, Mehmet; Prigent, Gaëtan
Abstract: The working frequencies of telecommunication systems are rapidly increasing and sub‐THz applications will soon be required. In that context, the current article presents the synthesis of a tunable ring filter. The considered filter introduces a new degree of freedom that allows to meet targeted specifications in terms of central frequency and bandwidth. Thanks to a capacitor displacement, the equivalent characteristic impedance can be tuned independently of its equivalent electrical length. The existing filter synthesis is modified to take this concept into account and thus provide a synthesis tunable in central frequency and bandwidth. The proof‐of‐concept of the design procedure is achieved in SiGe BiCMOS 0.25 μm technology with the implementation and measurement of eight non‐tunable circuits in the D‐band.